TRADITIONS OF THE SAK-MASSAGET TRIBES - Noyibjon Maripdjonovich Khudoyorov; Samandarbek Sobirjon ugli Ruziboev (Journals Park Publishing, 2024)
The article consists of a scientific analysis of the special traditions of the Sak-Massaget tribes who lived in the ancient Central Asian region in the VIII-IV centuries BC based on the works of historians of ancient times and modern historians.
Keywords: Jikhon, Sikhon, Scythian culture, Miletus school, araks, Eastern Anatolia, androphagia, cannibalism, Neanderthal, Agribteroi.